Strategi Minimasi Biaya Produksi Tahu Simadu Cicadas dengan Metode Aggregate Planning - Fauzan, Muhamad Ridho; Sangadah, Hanik Atus; Baharta, Ridwan (Jurnal Optimalisasi, 2025)
Tofu is a protein-rich product derived from soybeans and is in high demand in Indonesia. One of the tofu producers in Subang is PD. Berkah Jaya with the trade name “Tahu Simadu Cicadas”. Labor in the production of tofu at PD. Berkah Jaya uses 8 workers. Every production of PD. Berkah Jaya does not use production planning, but only relies on the number of incoming orders. The purpose of this study is to determine the cost minimization strategy based on the aggregate planning method. The stages carried out are forecasting, aggregate planning and making a Production Master Schedule (JIP). Forecasting used is the Single Moving Average (SMA) and Weighted Moving Average (WMA) methods. Aggregate planning used is the labor control method and the mixed method with overtime. The best forecasting based on the error rate can use the WMA method with an MSE value of 115,885 and a MAPE value of 3.20%. Cost minimization is achieved by the mixed method with overtime which incurs a cost of Rp 74.189,915  while the labor control method is higher at Rp 78.727.759. The JIP is made based on aggregate planning data for the mixed method with overtime. The number of workers to be used is 8 workers with 6 working days per week and the use of overtime as much as 7.33 hours or 1,276 packs of tofu for the next 3 months.